Effective by precision algorithms for approximation of functions from the Gelder class by Fourier’s series - Kolomys, Olena (Physico-mathematical modelling and informational technologies, 2021)
Effective by precision algorithms for approximation of functions from the Gelder class by Fourier’s series, using the Fourier’s coefficients, calculated with high precision, are constructed, and the evaluations of their basic characteristics (precision and speed) are obtained.